Zero-temperature relaxation in spin-polarized Fermi systems - Naish, A. E.; Owers-Bradley, A.; Meyerovich, J. H.; Stepaniants, J. R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
We describe the effect of zero-temperature attenuation, which has been recently observed in spin dynamics of Fermi liquids, on various processes in helium and ferromagnetic systems. After a brief review of theoretical and experimental data on zero-temperature attenuation in transverse spin dynamics of helium systems, we discuss coupling between longitudinal and transverse processes, the Castaing instability in 3He and 3He-4He mixtures, and applications to pure ferromagnetic metals.